Personnel selection for the aviation security service based on the threshold aggregation method - Pavlovich Hachikyan , Pavel (International Journal of Engineering and Technology, 2024)
Aviation emergencies cause great property damage and claim many lives. The task of the aviation security service is strictly to follow the instructions for ensuring safety and prevent abnormal and emergency situations. The article is devoted to the problem of selecting the appli-cable personnel for the aviation security service. Analyzed the influence of the human factor on aviation safety. Discussed the existing methods of personnel selection in the aviation security service. Developed a method of selecting personnel for the aviation security service based on the threshold aggregation method.